The Effect Of Simon Says Activities In Enhancing Students’ Listening Skills At Smpn 14 Kota Serang - Eka Wahyu Setyawan; Yudi Juniardi; Welliam Hamer (Gudang Jurnal Multidisiplin Ilmu, 2024)
This research aimed to find the effect of Simon Says activities in enhancing students’ listening skill at SMPN 14 Kota Serang. Quantitative research method by implementing quasi-experimental study using Simon Says activities to enhancing students’ listening skill at SMPN 14 Kota Serang. The population was seventh-grade students with 2 classes as a sample. In this study, 37 students in the experiment class and 37 students in the control class made up the sample. The data were collected using listening pre-test and listening post-test as instruments. SPSS 22.0 were used to analysed the data. The result of the research was there was significant difference between experimental class and control class where experimental class score increased to 84.41, while the control class only increased to 74.05. The analysis showed that the mean score of post-test in the experimental class was higher than control class. The result of Independent Sample Test table in this study was 0.000 < 0.05. This value means that the alternative was accepted and the null hypothesis was rejected. It can conclude that there is significant effect of Simon Says activities in enhancing students’ listening skill at SMPN 14 Kota Serang.